Diagenetic Controls on Carbonate Reservoir Quality of Kujung I Formation in KE-2 Field, East Java Basin, East Java. - Rezky Aditiyo; Dwiharso Nugroho; Nurcahyo Indro Basuk; Riza Agustiana; Anom Prasetya (Jurnal Geosains Terapan, 2022)
Early Miocene Kujung I Formation in KE-2 Field is a shelf edge barrier reef on North Madura Platform, East Java Basin. It was subsequently modified in near surface and burial diagenetic environments. Study has been made to establish the paragenetic sequence and effect of diagenesis on reservoir quality. Rock type identification was conducted using Rock Quality Index (RQI) and Flow Zone Indicator (FZI) methods from routine core analysis data. Subsequently, thin section, SEM, and XRD analysis were carried out to find out the link between geological attributes and petrophysical properties. Five major facies were identified: skeletal packstone, larger foraminifera wackestone, larger foraminifera packstone, coral packstone, shale, rhodolithic packstone, rhodolithic grainstone, and larger foraminifera grainstone. Diagenetic process which formed pore type and pore size is likely geological attributes controlling rock type association. Fibrous and botryoidal cement formed during shallow marine diagenesis. Subsequent exposure to a meteoric diagenetic environment resulting in leaching of high Mg calcite and aragonite, created separate vugs, moldic porosity. Burial diagenesis has resulted in compaction and stylolitization. Post burial diagenesis may result touching-vugs porosity and permeability, primarily in grain-dominated facies. Studied interval then can be classified into 5 rock type (RT), those are RT A – touching vugs porosity, RT B – touching vugs dan separate vugs, RT C – interparticle and separate vugs, RT D – separate vugs porosity, RT E – interparticle and separate vugs porosity. The rock type could define the reservoir quality, thus important to further exploration and development planning in KE-2 Field.